EVALUATING STUDENTS’ VIEWS ON THE IMPORTANCE AND USEFULESSNESS OF CEFR IN SPEAKING TEST - CH’NG, Looi-Chin; MAHMUD, Farah Fadhliah; SAHARI, Siti Huzaimah; ARSHAD, Aqilah; GAFAR@ ABD GHAFFAR, Siti Zuraina (Issues in language studies, 2024)
The Common European Framework of Reference for Languages (CEFR) is crucial for speaking tests as it provides a standardised framework to assess and gauge language proficiency accurately and consistently. This research evaluates ESL students’ awareness and perceived usefulness of the CEFR in group discussions. Data were obtained from 105 diploma students from UiTM Sarawak and UiTM Alor Gajah using an online questionnaire. The results indicate a moderate level of CEFR awareness, although opinions on its impact and role in language assessment and goal setting were varied. Respondents generally view CEFR-aligned speaking tests positively, showing a favourable perception of its usefulness. However, some have expressed concerns that these tests could be potential obstacles in their efforts to improve their language skills. The study highlighted the need for further education and training on CEFR-aligned assessments to enhance students’ comprehension and confidence in language proficiency development. It also emphasises the importance of designing assessments that help learners overcome potential barriers to improving language proficiency.